2014
DOI: 10.5717/jenb.2014.18.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations of body composition, flexibility and injury risk with ACE, ACTN3 and COL5A1 polymorphisms in Korean ballerinas

Abstract: [Purpose]The purpose of this study was to exam the association of body composition, flexibility, and injury risk to genetic polymorphisms including ACE ID, ACTN3 RX, and COL5A1 polymorphisms in ballet dancers in Korea.[Methods]For the purpose of this study, elite ballerinas (n = 97) and normal female adults (n = 203) aged 18 to 39 were recruited and these participants were tested for body weight, height, body fat, fat free mass, flexibility, injury risks on the joints and gene polymorphisms (ACE, ACTN3, COL5A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 35 publications
4
45
3
1
Order By: Relevance
“…Like our findings, Kim et al (2014) polymorphisms including ACE ID, ACTN3 RX, and COL5A1 polymorphisms in Korean ballet dancers and reported that ACE ID and ACTN3 RX polymorphisms were related with ballerinas' physical performance. In their study, they analyzed 97 elite ballerinas and 203 controls and showed that 55.7% of their ballerinas had the RX genotype (8).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Like our findings, Kim et al (2014) polymorphisms including ACE ID, ACTN3 RX, and COL5A1 polymorphisms in Korean ballet dancers and reported that ACE ID and ACTN3 RX polymorphisms were related with ballerinas' physical performance. In their study, they analyzed 97 elite ballerinas and 203 controls and showed that 55.7% of their ballerinas had the RX genotype (8).…”
Section: Resultssupporting
confidence: 88%
“…In their study, they analyzed 97 elite ballerinas and 203 controls and showed that 55.7% of their ballerinas had the RX genotype (8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results of the analyses where we have defined associations between the body-built indices and injury-prevalence on different locations are particularly interesting. Most of the studies done so far examined the general prevalence of injury in relation to anthropometric and body-built indices [6,23]. The strength of the current study is that, to our knowledge, it is the first to examine how the body-built is potentially related to an isolated injury of DISCUSSION There were several most important findings of this study.…”
Section: Resultsmentioning
confidence: 80%
“…However, the injuries at 3 locations (ankle, foot and toes) were specifically related to the body-built. The previous research found a positive association between body-fat measures and injury occurrence in ballet and dancing [23]. While an endomorphic somatotype component explained the fatness and roundness of the body, the results of higher ankle-injury prevalence of those ballet dancers who have higher endomorphic component were therefore expected.…”
Section: Resultsmentioning
confidence: 84%